Characteristics of helium DC plasma jets at atmospheric pressure with multiple cathodes - 王城 张泽龙 崔海超 夏维珞 夏维东 (Chinese physics B, 2017)
A novel DC plasma torch with multiple cathodes is developed for generating laminar, transitional and turbulent plasma jets. The jet＇s characteristics, including jet appearance, voltage fluctuation, thermal efficiency, specific enthalpy, and distributions of temperature, pressure, and velocity, are experimentally investigated. The results show that as the gas flow rate increases, the plasma jet transforms first from the laminar state to the transitional state and second to the turbulent state. Compared with the transitional/turbulent jet, the laminar jet possesses not only a better stability and a longer hightemperature zone but also a higher average/core temperature and a higher specific enthalpy at the nozzle＇s outlet. With the change of jet states from the laminar to the turbulent flow, the core pressure and velocity at the nozzle＇s outlet increase,while the decaying rates of temperature/pressure/velocity along the jet＇s axial direction increase sharply. Furthermore, applications of laminar, transitional and turbulent jets for zirconia spray coating are described. The test results indicate that the long laminar jet is favorable for the deposition of a high-quality coating because the powder particles injected into the laminar jet may have better heating and lower kinetic energy.